Peranan Pemerintah Desa dalam Pengadaan Mesin Diesel di Desa Bokori Kecamatan Soropia Kabupaten Konawe - Mansur, Mansur; Nalefo, La; Wunawarsih, Ima Astuty (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This is the process of procuring diesel engines in the village of Soropia district, Konawe district. This type of research is descriptive with qualitative method analysis. In qualitative research does not use the population, but still knows the term sample, using purposive sampling technique, is a technique of determining the number of people and 9 people. data processing that is analyzed by triggered techniques is checking the validity of data from all informants related to research. Results Research addresses the role of the village government in the procurement of diesel engines, including guidance to the community, service to the community and development of the community. These three variables have not gone well because there are still people who have not received good servants. While the procurement of diesel engines includes planning, setting, utilization, and reporting.